Borate–fructose complex: A novel mediator for laccase and its new function for fructose determination. Issue 20 (31st August 2015) - Cheng, Chih-Yu; Liao, Chia-I.; Lin, Shuen-Fuh
Abstract : Laccase and borate–fructose complex were investigated by coincidence in a solid‐state fermentation of Edenia sp. TS‐76 under fructose oxidase screening. Laccase was purified to homogeneity with a 34‐fold purification and 32% yield. Fructose had no significant effect on laccase activity, whereas borate reduced laccase activity by 60–90%; conversely, the borate–fructose complex increased laccase activity by nearly fourfold at pH 7.5. The complex caused a shift in the optimal pH for laccase from 5.0 to 7.5 and served as a highly efficient mediator. Borate complexed with fructose provides an alternative, time‐saving, and specific method for serum fructose determination. Abstract : Quantitative analysis of fructose by self‐assembling with borate to form a primary mediator. The possibility of glycosides to be substrates/mediators for laccase. Borate–fructose complex, a novel mediator with high efficiency at higher pH. Purification and identification of the first found laccase of Edenia sp. Investigation into laccase activation in the presence of borate and fructose.